Internationalisation of small and medium software firms from India. (1st January 2013) - Hajela, Ashish; Akbar, M.
The growth of small and medium enterprises (SMEs) has been a distinct feature of globalisation. This paper empirically studies the impact of internationalisation on performance of SMEs. This paper also explores the effects of geographic scope and international experience on SME performance. Based on secondary data for 29 software SMEs from India for the period 2002 to 2008, this paper finds a positive effect of internationalisation on firm performance. Drawing from multiple theoretical viewpoints, this paper discovers that while geographic scope is significantly related with SME performance, international experience has a weak association with SME performance. This paper contributes to the study of internationalisation-performance relationship of Indian software SMEs by empirically validating the positive relationship between internationalisation and performance among SMEs. The results imply internationalisation in diverse geographies and establishment of systems which facilitate knowledge transfer among firm's entities for realising superior returns.